A comprehensive review on glucokinase activators: Promising agents for the treatment of Type 2 diabetes. (10th November 2021) - Thilagavathi, Ramasamy; Hosseini‐Zare, Maryam Sadat; Malini, Manokaran; Selvam, Chelliah
Abstract: Glucokinase is a key enzyme which converts glucose into glucose‐6‐phosphate in the liver and pancreatic cells of the human. In the liver, glucokinase promotes the synthesis of glycogen, and in the pancreas, it helps in glucose‐sensitive insulin release. It serves as a "glucose sensor" and thereby plays an important role in the regulation of glucose homeostasis. Due to this activity, glucokinase is considered as an attractive drug target for type 2 diabetes. It created a lot of interest among the researchers, and several small molecules were discovered. The research work was initiated in 1990. However, the hypoglycemic effect, increased liver burden, and loss of efficacy over time were faced during clinical development. Dorzagliatin, a novel glucokinase activator that acts on both the liver and pancreas, is in the late‐stage clinical development. TTP399, a promising hepatoselective GK activator, showed a clinically significant and sustained reduction in glycated hemoglobin with a low risk of adverse effects. The successful findings generated immense interest to continue further research in finding small molecule GK activators for the treatment of type 2 diabetes. The article covers different series of GK activators reported over the past decade and the structural insights into the GK‐GK activator binding which, we believe will stimulate the discovery of novel GK activators to treat type 2 diabetes. Abstract : 2‐D interaction diagram with crucial interactions between glucokinase and glucokinase activator.